Assessment of Diagnostic Accuracy of Interleukins and Procalcitonin in Patients with Severe Illness and Suspected Sepsis: Interleukins and Pro-calcitonin in Severe Illness and Suspected Sepsis - Hayee Phulpoto, Abdul; Kumar, Mahesh; Aziz, Asif; Memon, Abdul Qayoom; Channa, Munir Ahmed; Parvez, Safdar Ali (Pakistan Journal of Health Sciences, 2024)
The immune system’s dysregulated response to infection, known as sepsis, is a severe potentially fatal illness that results in organ failure, tissue destruction, and systemic inflammation. Objectives: To explore the correlation between levels of interleukins and pro-calcitonin and the severity of sepsis and clinical outcomes. Methods: This cross-sectional study was conducted at Khairpur Medical College Civil Hospital Khairpur. The participants were n=200 including both male and female. The age range was 18-45 years. Procalcitonin levels were measured using enzyme-linked fluorescent assay and flow cytometry to elevate levels of different cytokines. Serum cytokine concentrations were compared between sepsis patients and healthy controls using the Mann-Whitney U-test for two-group comparisons. The diagnostic accuracy of cytokine levels at study entry was assessed through the area under the receiver operating characteristic curve derived from logistic regression analysis. Results: A positive culture report of microbial infectious disease was found in 100/200 (50%) of the patients after microbiological investigation. The male-to-female ratio in the investigated demographic was 3:2. Interleukin-6 levels were significantly higher, p<0.001 in the infectious diseases group than non-infectious Diseases Group. The area under the receiver operating characteristic value of interleukin-6 was found to be excellent and significantly higher (0.95(0.75-0.97)). Conclusions: Cytokines including Interleukin-6 and Interleukin-8 are strong biomarkers for diagnosing microbial infections in suspected sepsis cases, with interleukin-6 showing the highest diagnostic accuracy (AUC=0.912). Procalcitonin also demonstrated good discriminative power (AUC=0.895). While cytokines like Interleukin-2, tumor necrosis factor, and Interleukin-17A showed moderate value, interleukin-4 and interferon-gamma were less useful.